International Conference on Eurasian Economies 2016 2016
DOI: 10.36880/c07.01715
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth-Migration Nexus: An Analysis Based on Developing Countries

Abstract: Relations between migration and economic growth have been shaped around both positivist and Non-positivist ideas in the economic literature. Approaches based on the Positivist argument mostly views the effect of migration on economic growth through the lens of human capital and brain drain while Non-positivist argument approaches the issue in terms of the negative effects of unqualified labor. On the other hand, increasing migration at the international level has been gaining importance since immigrants create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The notion that skilled immigrants reduce the negative impact on GDP is supported by studies such as Dolado et al (1994) and Barro and Sala-i-Martin (2004). The findings of Ahmed (2010), Sevinç andSevinç Eroğlu. (2016), andŞimşek (2018) are consistent with the conclusion that an increase in the number of immigrants negatively affects GDP.…”
Section: Hypothesizedmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that skilled immigrants reduce the negative impact on GDP is supported by studies such as Dolado et al (1994) and Barro and Sala-i-Martin (2004). The findings of Ahmed (2010), Sevinç andSevinç Eroğlu. (2016), andŞimşek (2018) are consistent with the conclusion that an increase in the number of immigrants negatively affects GDP.…”
Section: Hypothesizedmentioning
confidence: 99%
“…Regarding the relationship between international migration and Gross Domestic Product (GDP), some studies have found a positive impact of migration on GDP (Felbermayr et al, 2010;Boubtane et al, 2013;Ortega and Peri, 2014;Engin and Konuk, 2020;Gülbahar, 2020), while others report a negative impact (Ahmed, 2010;Sevinç and Sevinç Eroğlu, 2016;Şimşek, 2018). Studies examining the direction of causality between migration and GDP have distinguished between one-way causality, with GDP being the cause of migration (Morley, 2006) or migration being the cause of GDP (Göv and Dürrü, 2017;Şimşek, 2018;Meçik and Koyuncu, 2020) and bidirectional causality (Feridun, 2004;Altunç et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They added that the socio-economic development variable alone is insufficient to explain the migration rate; therefore, political, cultural, and demographic factors should also be included in the model [15]. Sevinç et al [51] examined the relationship between migration and economic growth in developing countries between the years of 1962-2012. They found that in Turkey, there is a significant and negative relationship between economic growth and migration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She found that the unemployment rate, inflation, and property rates increased at a higher rate in regions where Syrians live most. The studies focused on Syrian refugees mostly examined housing and labour market changes and inflation [51,54].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Qutb (2021) emphasized the long-term negative impact of remittances on economic growth in Egypt and warned against the simultaneous perception of the positive aspects of such remittances. Sevinç et al (2016) investigated the relationship between migration and economic growth in 18 developing countries for the period 1962-2012 using panel data methods. According to the findings of the study, the negative impact of migration on economic growth was found.…”
Section: İbrahim Halil Sugözü Nuraiym Talantbekova Migration Remitta...mentioning
confidence: 99%